2002
DOI: 10.1002/jez.10077
|View full text |Cite
|
Sign up to set email alerts
|

Expression and biological effect of urodele fibroblast growth factor 1: Relationship to limb regeneration

Abstract: Fibroblast growth factors (FGFs) have been previously implicated in urodele limb regeneration. Here, we examined expression of FGF-1 by blastema cells and neurons and investigated its involvement in wound epithelial formation and function and in the trophic effect of nerves. Neurons innervating the limb and blastema cells in vivo and in vitro expressed the FGF-1 gene. The peptide was present in blastemas in vivo. Wound epithelium thickened when recombinant newt FGF-1 was provided on heparin-coated beads, demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…The constant formation of limb outgrowths after FGF treatment in our experiments suggests that these proteins, like in embryonic limb buds [26,31], are one of the signaling and growth molecules needed for limb (ant tail) regeneration in lizard, as this was long indicated for amphibians [32]. The present study has shown that both FGF1 and FGF2 stimulates the regeneration of the limb, in particular of the stilopodium (cartilaginous femur) and of the two zeugopodium elements, partially or completely subdivided in cartilaginous tibia and fibula.…”
Section: Fgfs Mainly Stimulates Limb and Bone Regenerationmentioning
confidence: 95%
“…The constant formation of limb outgrowths after FGF treatment in our experiments suggests that these proteins, like in embryonic limb buds [26,31], are one of the signaling and growth molecules needed for limb (ant tail) regeneration in lizard, as this was long indicated for amphibians [32]. The present study has shown that both FGF1 and FGF2 stimulates the regeneration of the limb, in particular of the stilopodium (cartilaginous femur) and of the two zeugopodium elements, partially or completely subdivided in cartilaginous tibia and fibula.…”
Section: Fgfs Mainly Stimulates Limb and Bone Regenerationmentioning
confidence: 95%
“…The urodele AEC is known to express Fgf8 (Han et al, 2001;Christensen et al, 2002) and to accumulate FGF1 and FGF2 peptides (Mullen et al, 1996;Dungan et al, 2002;Giampaoli et al, 2003), but there are few functional studies that test the role of FGFs in regeneration. Details of the expression pattern of Fgf family members suggest that there are key differences between the AER of amniote limb buds and the AEC of urodele regenerating limbs.…”
Section: Wound Healing and Dedifferentiationmentioning
confidence: 98%
“…In urodeles, the initial response to the injury is the formation of a fibrin clot that covers the wound surface and provides a substrate on which peripheral epidermal cells migrate to close the wound (Donaldson et al, 1985(Donaldson et al, , 1987. This process is initiated by cells at the wound edge extending lamellipodia and actively moving across the wound, and more proximal cells similarly extending lamellipodia behind these lead cells (Mahan and Donaldson, 1986;Dungan et al, 2002). Urodele wound closure occurs incredibly fast; in young axolotls, an amputation wound is closed within 4 hr (Carlson et al, 1998), and in the adult newt, wound closure is completed in less than 12 hr (Repesh and Oberpriller, 1978).…”
Section: Wound Healing and Dedifferentiationmentioning
confidence: 99%
“…Factors other than AGP that promote blastema cell proliferation in vitro have been detected in the wound epidermis of the regenerating limb, including Fgf-1, 2, and 8 (Chew and Cameron, 1983;Boilly et al, 1991;Zenjari et al, 1997;Han et al, 2001;Christensen et al, 2001Christensen et al, , 2002Dungan et al, 2002;Giampaoli et al, 2003). Likewise, nerves produce other mitogens including transferrin, Fgf-2, Ggf-2 (neuregulin), and substance P (Munaim and Mescher, 1986;Mescher and Kiffmeyer, 1992;Mescher et al, 1997;Globus and Alles, 1990;Anand et al, 1987;Mullen et al, 1996;Wang et al, 2000).…”
Section: Blastema Cell Proliferationmentioning
confidence: 99%